Salt spray fog ageing of hybrid composite/metal rivet joints for automotive applications. (1st January 2017) - Fiore, V.; Calabrese, L.; Proverbio, E.; Passari, R.; Valenza, A.
Abstract: The present experimental investigation aims to investigate the effect of salt-fog exposition on the mechanical behaviour of composite/metal riveted joints. To this aim, two kinds of joint were exposed to salt-fog environmental conditions according to ASTM B117 standard, for fifteen weeks. In particular, two composite laminates (i.e. glass fibre and carbon fibre/epoxy composites) were used as composite substrate joined with the metal substrate (i.e. aluminium alloy Al 6060). Single-lap shear tests were carried out in order to evaluate the evolution of the mechanical performances and the damage mechanisms of the riveted joints during the ageing exposition. The results evidence that the mechanical performances (i.e. maximum load and load-displacement slope) of the hybrid joints progressively decrease at increasing ageing time in the considered exposure time. Moreover, glass fibre/epoxy hybrid composite joint showed a higher sensitivity to degradation in salt-fog environmental condition than carbon fibre/epoxy one. As concerns the damage mechanisms, glass fibre/epoxy hybrid composite joint experienced catastrophic cleavage/net tension failure modes regardless the ageing time whereas the progressive bearing failure was the mechanism observed in carbon fibre/epoxy hybrid composite joint during the entire experimental campaign. Corrosion phenomena not significantly affected degradation performances of both joints.